2019
DOI: 10.6061/clinics/2019/e1231
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of patients with preterm premature rupture of membranes at a tertiary hospital in São Paulo, Brazil

Abstract: OBJECTIVE:To perform a descriptive analysis of preterm premature rupture of membranes (PPROM) cases attended in a tertiary hospital.METHOD:Retrospective analysis of medical records and laboratory tests of patients admitted to a Brazilian tertiary hospital between 2006 and 2011, with a confirmed diagnosis of PPROM and gestational age (GA) at delivery <37 weeks.RESULTS:A total of 299 pregnant women were included in the study. Nine patients evolved to abortion, and 290 pregnant women remained for the final analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 50 publications
(84 reference statements)
2
9
0
Order By: Relevance
“…Majority respondents were in age group 26-30 years (36.7%) with a mean age of 27.03 ±6.13 years. The average maternal age of our subjects showed similarity with that reported in some other studies; those values were 27.46 years in Galletta et al's study 16 26.36 years in Flores's study. 17 In contrast, our patients had a lower average maternal age than those reported by Dars et al 18 , 30 years by Frenette et al 19 , 29.7 years by Garite et al 20 Higher maternal age could be related to the more frequent presence of maternal diseases, such as hypertension and diabetes, or obstetric pathologies, such as twinning and fetal malformations.…”
Section: Discussionsupporting
confidence: 91%
“…Majority respondents were in age group 26-30 years (36.7%) with a mean age of 27.03 ±6.13 years. The average maternal age of our subjects showed similarity with that reported in some other studies; those values were 27.46 years in Galletta et al's study 16 26.36 years in Flores's study. 17 In contrast, our patients had a lower average maternal age than those reported by Dars et al 18 , 30 years by Frenette et al 19 , 29.7 years by Garite et al 20 Higher maternal age could be related to the more frequent presence of maternal diseases, such as hypertension and diabetes, or obstetric pathologies, such as twinning and fetal malformations.…”
Section: Discussionsupporting
confidence: 91%
“…Review of literature shows that among PPROM patients, the incidence of PPROM in previous pregnancies were 5.4%, 6.6% and 11.8% in studies by Silveira et al, Galletta et al, and Kilpatrick et al, respectively. [6][7][8] Getahun et al found that the risk of PPROM increased by a factor of 2 to 2.4 in patients of PPROM with previous history of PPROM. 9 In the present study, of the 89 multiparous women only 2.2% had history of PPROM in previous pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…respectively with far lesser rates in control group of Zhang et al (6.5%) suggesting GBS infection as a risk factor for PPROM. 7,[13][14][15] Hence some authors recommend chemoprophylaxis for GBS during intrapartum to decrease the incidence of early-onset neonatal GBS sepsis and mortality unless a negative perineal culture for GBS has been documented within the previous 5 weeks. 16 However, RCOG guidelines 2017 recommended routine use intrapartum antibiotic prophylasis for GBS irrespective of GBS carrier status.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported [35][36][37] that for PPROM patients who have fetal lung maturity and infection, simply extending the gestational week will not reduce the serious complications of preterm infants, but PPROM pregnant women have reduced amniotic fluid, higher incidence of chorioamnionitis and various inflammations in the amniotic fluid. The increase in substances can affect the growth and development of the fetus, causing the fetal body mass to not increase correspondingly with the growth of the gestational age.…”
Section: P R E P R I N Tmentioning
confidence: 99%